Personal information management systems: A user-centric privacy utopia? - Heleen Janssen; Jennifer Cobbe; Jatinder Singh (Internet Policy Review, 2020)
Personal information management systems (PIMS) aka personal data stores (PDSs) represent an emerging class of technology that seeks to empower individuals regarding their data. Presented as an alternative to current 'centralised' data processing approaches, whereby user data is (rather opaquely) collected and processed by organisations, PDSs provide users with technical mechanisms for aggregating and managing their own data, determining when and with whom their data is shared, and the computation that may occur over that data. Though arguments for decentralisation may be appealing, there are questions regarding the extent to which PDSs actually address data processing concerns. This paper explores these questions from the perspective of PDS users. Specifically, we focus on data protection, including how PDSs relate to rights and the legal bases for processing, as well as how PDSs affect the information asymmetries and surveillance practices inherent online. We show that, despite the purported benefits of PDSs, many of the systemic issues of online/data ecosystems remain.
Keywords: 300; Personal data stores; Decentralisation; User empowerment; General Data Protection Regulation